Development of Project Based Learning Science Teaching Modules Integrated Entrepreneurship For Increase Students’ Mastery of Concepts - Ida Trisnawati; Mohammad Masykuri; Sri Yamtinah (IJIS Edu : Indonesian Journal of Integrated Science Education, 2025)
The development of the science teaching module project based learning integrated entrepreneurship aims to determine the characteristics of the science teaching module project based learning integrated entrepreneurship in improving students' concept mastery learning outcomes and knowing the effectiveness of science project based learning integrated entrepreneurship in improving students' concept mastery learning outcomes. This development research uses the research and development method (Research and Development) which uses the Four D model, which includes the definition stage, design stage, development stage and disseminate stage. The population in this study were class VII junior high school students. The research sample consisted of 62 students consisting of class VII D students as the experimental class and class VII E students as the control class. The experimental class uses the PjBL model teaching tools with integration of entrepreneurship while the control class uses a conventional model according to the school teacher's. The results of research and development show that the characteristics of the PjBL science teaching module are integrated with entrepreneurship by developing the syntax of the PjBL model with aspects of entrepreneurial attitudes empowered in each learning activity syntax. The PjBL integrated entrepreneurship science teaching module is effective in improving student learning outcomes as evidenced by the average N-Gain Score in the experimental class being 0.76 which is included in the high or effective category and the average N-Gain score in the control class is 0.52, which is included in the moderate or less effective category. It was concluded that students' mastery of concepts taught using Project Based Learning-based science teaching tools integrated with Entrepreneurship was better than students who did not use these teaching tools.